PENGARUH MODEL KOOPERATIF TIPE STAD TERHADAP HASIL BELAJAR PENDIDIKAN PANCASILA SISWA KELAS IV SEKOLAH DASAR - Dinda Novitasari; Ramanata Disurya, Farizal Imansyah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to determine the effect of the STAD type cooperative model on the learning outcomes of Pancasila Education of grade IV students of SD Negeri 96 Palembang. This study is a quantitative study using a one group pretest and posttest design with a total sample of 20 students. The data collection technique used was a test consisting of 10 multiple choice questions. Based on the results of the study from the final results of the data analysis, the Posttest score had a higher average score compared to the average pretest score, namely the average Posttest score of 83.00 while the average Pretest score was 53.00. With a significant value (2-tailed) of 0.000 and a t table of 0.05, the sig. value. (2-tailed) ≤ t table or 0.000 ≤ 0.05 which means that there is an influence of the STAD type cooperative model on the learning outcomes of Pancasila education of grade IV students of SD Negeri 96 Palembang